Dynamic identification and condition assessment of an old masonry chimney by using modal testing. (2017) - Sancibrian, R.; Lombillo, I.; Sarabia, E.G.; Boffill, Y.; Wong, H.; Villegas, L.
Abstract: The renovation of old industrial sites for modern use requires the knowledge of the health status of old structures in order to ensure their use in safety conditions. The main goal of this paper is to assess the dynamic behavior of a masonry industrial chimney built in Spain in the early XX century. The paper also focuses on determining health status of the structural system and understanding where the errors and uncertainties of the numerical modelling are originated. The chimney is 38.30 m high and is founded on a concrete truncated pyramid. The paper shows the different test carried out in laboratory to obtain the mechanical parameters of the materials by means of analyzing the bricks and mortar before doing the dynamic study. After that, the chimney has been monitored for the study of the dynamic behavior and the results provided from the ambient-vibration and modal testing are presented in the paper. To this aim, Operational Modal Analysis (OMA) is used to determine the dynamic characteristics of the chimney including natural frequencies and modes shapes. The outcomes of the experimental analysis have been compared with the numerical results updating the Finite Element (FE) model used for the theoretical simulation of the chimney. The results show that the health status of the chimney is satisfactory and the combination of gravitational and wind loads do not supposes a risk for the physical integrity of the structure.